Tussen erfgoed en eredienst Meervoudig gebruik van vier monumentale stadskerken - Kuyk, Elza (Amsterdam University Press, 2023)
Some multiple-used city churches are neither fully in use by a faith community nor fully allocated to new forms of use, but are shared by both a (protestant) faith community and secular users. By sharing the church building, the diverse users and communities get in touch with each other. Eventual (slight) offenses between them can often be traced back to their respective relationships with the church building. Each church building has a specific history of the use of the building, its own architecture, a specific Protestant community, a chosen legal model and a particular profile for multiple use. Through the multiple use and the restorations, the pre-Reformation Catholic past is tangibly brought back. Those involved realise that they depend on each other in their efforts to keep the church building in good condition. The analysis of the interactions between users concentrates on the tangible aspects of the process of de-churching.